Preserving Cultural Heritage in a Digital World: Balancing tradition, inclusivity, and sustainability - Calista, Avniela; Fitriningtyas, Ika Devy (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2024)
Carnaval, a global festival with deep historical and cultural roots, has evolved from ancient pagan rituals into a vibrant expression of community identity, creativity, and joy. This paper analyzes the global trends in Carnaval celebrations and their evolving meanings in the digital age, with a focus on balancing tradition, inclusivity, and sustainability. By examining how digital technologies reshape the experience and dissemination of Carnaval, this study highlights the interplay between globalization, cultural continuity, and change. Case studies from Brazil, Trinidad and Tobago, Venice, New Orleans, and Indonesia illustrate the integration of digital tools in promoting and preserving Carnaval traditions. The findings reveal that while digital platforms enhance accessibility and inclusivity, they also pose challenges in maintaining cultural authenticity. By leveraging augmented reality, virtual reality, live streaming, and social media, Carnaval events can reach a global audience, fostering cultural exchange and appreciation. However, it is crucial to balance these innovations with the preservation of traditional elements to ensure the essence and historical significance of Carnaval are maintained. This paper concludes with recommendations for stakeholders to integrate digital technology responsibly, promoting sustainable practices and inclusive participation while preserving the rich cultural heritage of Carnaval.